Investigation into the onset and progression of transplant arteriosclerosis in a mice aortic retransplantation model. - Steger, U; Ensminger, S; Bushell, A; Wood, K (2008)
Long-term function of vascularized human organ grafts is often limited by transplant arteriosclerosis and can lead to graft failure. Here, we have analyzed the impact of an initial rejection episode on the later development of transplant arteriosclerosis. Following transplantation of allogeneic abdominal aortic segments in mice, aortic grafts were retransplanted into either immunodeficient or syngeneic recipients. Retransplantation of grafts from immunocompetent into immunodeficient mice as early as 2 days after the primary transplant resulted in intimal proliferation and obstruction of the graft lumen 30 days after the primary transplant. In contrast, retransplantation of the grafts into donor syngeneic B10 recipients within 7 days did not result in the development of transplant arteriosclerosis. These data suggest that the adaptive immune system can induce intimal proliferation by an initial lethal hit that is sustained by the innate response. However our data demonstrate that development of chronic rejection can be inhibited, in this case by retransplantation into a syngeneic host.